2008
DOI: 10.1186/1476-069x-7-59
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality in Peruvian pesticide applicators: association between urinary organophosphate metabolites and semen parameters

Abstract: Background: Organophosphates are broad class of chemicals widely used as pesticides throughout the world. We performed a cross-sectional study of associations between dialkylphosphate metabolites of organophosphates and semen quality among pesticide applicators in Majes (Arequipa), Peru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…The poorest semen quality was found among farmers with the highest OP exposure and the highest urinary OP levels. The results showed a significant decrease in total sperm count among subjects with the highest exposure to OP [48] (Table 4). In summary, there are several indications that some pesticides may impair semen quality in humans, but weak exposure assessment in most studies precludes proper identification of responsible agents and evaluation of exposure-response relations.…”
Section: R E V I E W P a P E R S Ijomeh 2009;22(4)mentioning
confidence: 91%
See 2 more Smart Citations
“…The poorest semen quality was found among farmers with the highest OP exposure and the highest urinary OP levels. The results showed a significant decrease in total sperm count among subjects with the highest exposure to OP [48] (Table 4). In summary, there are several indications that some pesticides may impair semen quality in humans, but weak exposure assessment in most studies precludes proper identification of responsible agents and evaluation of exposure-response relations.…”
Section: R E V I E W P a P E R S Ijomeh 2009;22(4)mentioning
confidence: 91%
“…The next study where the exposure to carbaryl and chlorpyrifos was analysed by detecting the urinary metabolites showed an associated between exposure and lower sperm concentration and motility among men attending an infertility clinic [42] (Table 4). Yucra et al [48] reported a significant reduction of semen volume and an increase in semen pH in men with organophosphate metabolites in urine in the study performed in Peru [48]. The poorest semen quality was found among farmers with the highest OP exposure and the highest urinary OP levels.…”
Section: R E V I E W P a P E R S Ijomeh 2009;22(4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most organophosphorus insecticides are mainly degraded to dialkylphosphates and phenolic metabolites in mammals [17]. To monitor human exposure to the insecticides, urinary dialkylphosphates have generally been measured in previous studies [18][19][20][21][22][23][24][25][26][27][28]. However, the parent compounds cannot be identified from urinary dialkylphosphates because they are common metabolites resulting from most organophosphorus insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Recio-Vega et al [31] found that among men with high urinary organophosphate pesticide (OP) levels, the total sperm count was significantly decreased. Yucra et al [32] found a significant association between high levels of ethylated OP metabolites in urine and low seminal volume in Peruvian pesticide applicators. In addition, a case-control study in the People's Republic of China found that men with higher urinary levels of OP dimethylphosphate metabolites were more likely to have low sperm motility and concentration [33].…”
Section: Introductionmentioning
confidence: 99%